2020
DOI: 10.1021/acsami.0c10310
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the Phase Segregation with Potassium for Highly Efficient and Photostable Inverted Wide-Band Gap Halide Perovskite Solar Cells

Abstract: Wide-band gap (WBG) mixed-halide perovskites have drawn much attention because of their excellent optoelectronic properties and the potential to be deployed in tandem solar cells. Nevertheless, the bromine incorporation inevitably leads to photoinduced phase segregation in WBG mixed-halide perovskites. Herein, potassium is used to effectively suppress photoinduced phase segregation, which is visualized with confocal photoluminescence microscopy imaging. Strikingly, the potassium passivation not only inhibits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Moreover, it is among the highest PCEs reported for polymer HTL-based 3D IPVSCs. [18,25,[52][53][54][55][56][57][58][59][60][61][62][63][64][65]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is among the highest PCEs reported for polymer HTL-based 3D IPVSCs. [18,25,[52][53][54][55][56][57][58][59][60][61][62][63][64][65]…”
Section: Resultsmentioning
confidence: 99%
“…[80,85] K + decorates the grain boundaries rather than being doped into the perovskite lattice, which can substantially mitigate both non-radiative recombination losses and photoinduced ion migration in perovskite films and interfaces. Liang et al deployed K + in FA 0.8 Cs 0.2 Pb(I 0.7 Br 0.3 ) 3 perovskites (E g = 1.7 eV), [85] which significantly suppressed phase segregation and reduced the voltage loss from 152 to 95 mV. Therefore, the KI-modified WBG PSCs yielded a high V OC of 1.19 V along with a PCE of 18.3%.…”
Section: Additive Engineeringmentioning
confidence: 99%
“…Moreover, MA þ cation doping would reduce thermal stability due to its easy volatilization from perovskite lattices [26,83,84] and Br À doping might undergo phase segregation because of ion migration. [85][86][87] New doping ions should be developed to stabilize the α-phase while maintaining the inherent bandgap of FAPbI 3 . It was reported that methylenediammonium dichloride (MDACl 2 ) additive improved phase stability and photovoltaic performance.…”
Section: Composition Engineeringmentioning
confidence: 99%